2020
DOI: 10.1371/journal.pone.0235391
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal septicemia at intensive care unit, Ayder Comprehensive Specialized Hospital, Tigray, North Ethiopia: Bacteriological profile, drug susceptibility pattern, and associated factors

Abstract: Background Neonatal septicemia is a life threatening medical emergency that requires timely detection of pathogens with urgent rational antibiotics therapy. Methods A cross-sectional study was conducted between March 2017 to September 2018 among 317 septicemia suspected neonates at neonatal intensive care unit, Ayder Comprehensive Specialized Hospital, Mekelle, Tigray, North Ethiopia. A 3 mL of blood was collected from each participant. Identification of bacterial species was done using the standard microbiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…The prevalence of neonatal sepsis in the present study is 36.5% of which 53.1% were early-onset and 46.9% were late-onset sepsis. The finding is in agreement with studies conducted in different parts of Ethiopia and other countries (30–36%) 4 , 11 17 . In contrast to our study, lower than 30% prevalence of neonatal sepsis was reported in Southeast Ethiopia 3 , India 18 ; and less than 20% prevalence was reported in Pakistan 13 , Ghana 19 , Uganda 20 , Kenya 21 , and Nepal 22 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The prevalence of neonatal sepsis in the present study is 36.5% of which 53.1% were early-onset and 46.9% were late-onset sepsis. The finding is in agreement with studies conducted in different parts of Ethiopia and other countries (30–36%) 4 , 11 17 . In contrast to our study, lower than 30% prevalence of neonatal sepsis was reported in Southeast Ethiopia 3 , India 18 ; and less than 20% prevalence was reported in Pakistan 13 , Ghana 19 , Uganda 20 , Kenya 21 , and Nepal 22 .…”
Section: Discussionsupporting
confidence: 93%
“…The etiology of neonatal sepsis is heterogeneous; it varies from country to country; for instance, S. agalactiae was among the leading cause of neonatal sepsis in the United States until Intrapartum Antibiotic Prophylaxis, a prevention strategy, was implemented 12 . However, this bacterium is rarely isolated from newborns suspected of sepsis in Ethiopia 4 , 11 . The prevalence of neonatal sepsis in the present study is 36.5% of which 53.1% were early-onset and 46.9% were late-onset sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 The standard method to determine whether a neonatal septicemia is in progress is a positive blood culture. 8 There were considerable variations in septic microorganisms in the neonatal intensive care unit (NICU). In earlier studies in China, it was found that Klebsiella Pneumoniae was the most common bacteria causing neonatal septicemia, followed by Staphylococcus Aureus .…”
Section: Introductionmentioning
confidence: 99%
“…The review was conducted among 20 109 live births delivered after 28 weeks of gestation to estimate the pooled effect of preterm birth on adverse outcomes. Of those, 8 studies reported perinatal mortality, 24 , 25 , 49 52 3 studies 53 55 reported stillbirth, 9 studies 27 , 56 63 reported neonatal sepsis, 4 studies 26 , 64 – 66 were on neonatal hypothermia and 8 studies 28 , 67 74 reported neonatal mortality. Regarding the design of the included studies, sixteen (48.5%) were cross-sectional studies, 26 , 49 , 51 , 53 , 56 , 58 , 60 , 64 , 66 , 68 , 72 74 8 (24.2%) studies were case-control 24 , 25 , 50 , 52 , 54 , 59 , 60 ,…”
Section: Resultsmentioning
confidence: 99%